Comparison of cardiovascular events and estimation of hazard ratio for hypertensive patients with and without hypertensive urgencies after a 12-month follow up. (14th October 2021) - Fragoulis, C; Dimitriadis, K; Konstantinidis, D; Tatakis, F; Kariori, M; Kalos, T; Thomopoulos, C; Androulakis, G; Tousoulis, D; Tsioufis, K
Abstract: Background: Few epidemiological data show a worst prognosis of hypertensive emergencies compared with hypertensive urgencies (HU). To the best of our knowledge, there is even fewer published evidence comparing prognosis of hypertensive patients (HP) with and without HU. Purpose: The purpose of our prospective study was to record the prevalence and clinical characteristics of patients with HU assessed in the emergency department (ED) in a tertiary Hospital and to compare them with HP without urgencies for new events and hard-end points for a 12-month follow-up. Methods: The study population consisted of 256 patients presenting at the ED with acute increase in blood pressure (BP) (systolic BP≥180mmHg and/or diastolic BP≥120mmHg) with absence of acute hypertension-mediated target organ damage in a period of one year. Each of these participants were matched one-to-one by age, gender and history of hypertension with HP with either controlled, grade 1 or grade 2 hypertension attending our Hypertension excellence center the same period. However, 78 of HU did not conclude the follow up and 5 could not be matched with HP for the above covariates and were therefore excluded. Both groups, 173 of HU and 173 of controls, concluded 12 months follow up for fatal and non fatal cardiovascular events, including acute coronary syndrome, stroke, newly diagnosed heart failure or deterioration of NYHA class, and composite end points such as stroke-myocardial infarction and overall cardiovascular disease outcome. Results: The mean age of all patients was 64.9±12.5 years (64±12.2 for controls and 65.7±12.7 for HU), 48.8% were males (49.1% of controls and 48.6% of HU) and 26.6% had a history of smoking (22.5% of controls and 30.6% of HU). Overall, 15 (5.5%) patients had nonfatal clinical cardiovascular events and 4 (1.2%) had fatal cardiovascular events. Cox regression models were adjusted for age, gender, smoking, previous cardiovascular disease, diabetes mellitus and the population. The frequency of the composite stroke-myocardial infarction event was statistically significant higher in HU (5 vs 4, p<0.0001, Hazard Ratio for HU 181.7, 95% Confidence Intervals 19.7–1677.2) adjusted for the rest covariates. In addition, there was a higher trend for stroke in the group of HU (p=0.067) and in patients with a history of diabetes mellitus irrespective of group (p=0.055). Finally, the Cox regression analysis identified age (p=0.035) and history of cardiovascular disease (p=0.038) as independent predictors for death, and smoking (p=0.035) as independent predictor for overall cardiovascular events. Conclusions: Our study emphasizes the higher trend for cardiovascular outcomes, especially stroke, in the group of HU compared with HP without urgencies, while it highlights the necessity for more intensive follow-up for the first group and the need for further research in this pathological entity. Funding Acknowledgement: Type of funding sources: None.